STUDI KARAKTERISTIK SUB DAS SAMIH DAS LANDAK KABUPATEN LANDAK - Iyas, Leosius; Saifudin, Ir. Saifudin, M. Si; Junaedi, Ir. Junaidi, MP. (Jurnal Sains Pertanian Equator, 2013)
STUDY OF THE CHARACTERISTICS OF SAMIH SUB WATERSHED AND LANDAK WATERSHED KABUPATEN LANDAK Leosius Iyas (1), Ir. Saifudin , M.Si (2) and Ir. Junaidi, MP (2) (1) a student of agriculture faculty and (2) lecturers at agriculture faculty of Tanjungpura University, Jl. A. Yani Pontianak 78124 ABSTRACT This research was to figure out and to study thr charachteristics of Samih sub-watershed in Landak Regency. This research was located in Samih watershed and was conducted in two stages. The first stage was to collect the water as sample in one outlet, which was in Sebangki Village in Sebangki District. Then, the next stage was to analyze the samlpe which was conducted in Soil, Water, and Envinronment Analysis Lab of Agriculture Faculty, Tanjungura University. According to the result of the analysis, it could be concluded that the water quality found in Samih watershed consist of: average of acidity as much 5.91. This indicator showed that the condition of Samih sub-watershed categorized into “good”. The average temperature Samih sub-watershed was as much 27.200C and that was categorized into normal within tropical climate. Meanwhile, the brightness level of the water in Samih syb-watershed was 59.80 cm, with maximum depth as 4.59 m. The result of the research pointed out that the drainage pattern in Samih sub-watershed took form as dendritics pattern and longitudinal as bird’s feather, meanwhile its tranversal profile took triangle form. The subsidiary indexes in Samih sub-watershed were (17), (4), and (2). Besides, Samih sub-watershed possessed drainage density with values of 33.54 which was categorized as high and average discharge was 3.39 m2/s and average value of sedimentation flow was 4.78 tonne/day. Keywords: The Charachteristics of Sub Watershed, Samih Sub Watershed.